IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA NEGERI 1 SIBABANGUN - Bronika Septiani Sianturi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The purpose of this study is to determine whether STAD type cooperative learning is better than conventional learning models in improving student chemistry learning outcomes on the subject of atomic structure in class X SMA 1 Sibabangun. This research is an experimental research. The population in this study was all students of class X SMA 1 Sibabangun consisting of 3 classes. The research sample was selected 2 classes randomly, namely class X-1 as the experimental class using cooperative learning type STAD and class X-2 as the learning control class using conventional learning. From the data analysis for the experimental class, pre-tests (20.65 ± 6.47) and post-tests (90.8 ± 7.35) were obtained. In the control class, pre-tests (34.60 ± 8.45) and post-tests were obtained (70.55 ± 10.37). The results of testing the hypothesis by using the one-party t test at = 0.05 and dk = 62 obtained tcount>ttable or 4.425> 2.034 then Ha is accepted, Improving student learning outcomes after being given learning treatment Type STAD is better than conventional learning on the subject structure atom class X SMA Negeri 1 SibabangunKeywords: Implementation, Cooperative Type STAD, Learning Outcomes